An immunologist's guide to immunosenescence and its treatment. (2nd September 2022) - Caruso, Calogero; Ligotti, Mattia Emanuela; Accardi, Giulia; Aiello, Anna; Candore, Giuseppina
ABSTRACT: Introduction: Aging causes several changes in the immune system, although immune aging is strongly influenced by individual immunological history, as well as genetic and environmental factors leading to inter-individual variability. Areas covered: We focused on the biological and clinical meaning of immunosenescence. SARS-CoV-2 and Yellow Fever vaccine have demonstrated the clinical relevance of immunosenescence, while inconsistent results, obtained from longitudinal studies aimed at looking for immune risk phenotypes, have revealed that immunosenescence is highly context-dependent. Large projects allowed the delineation of the drivers of immune system variance, including genetic and environmental factors, sex, smoking, and co-habitation. Therefore, it is difficult to identify the interventions that can be envisaged to maintain or improve immune function in older people. That suggests that drug treatment of immunosenescence should require personalized intervention. Regarding this, we discussed the role of changes in lifestyle as a potential therapeutic approach. Expert opinion: Our review points out that age is only part of the problem of immunosenescence. Everyone ages differently because is unique in genetics and experience of life and this applies even more to the immune system (immunobiography). Finally, the review shows how appreciable results in the modification of immunosenescence biomarkers can be achieved with lifestyle modification.